CONSTITUTION OF REPUBLIC OF UZBEKISTAN (Ustozlar uchun, 2025)
This article is about the Constitution of the Republic of Uzbekistan. The constitution, which is a symbol of the nation, was created by whom and when, the law, substances and clauses are discussed.